Preparation method and application of monatomic and nanoparticle coexisting catalytic material

By preparing catalytic materials that coexist with single atoms and nanoparticles, the problems of low selectivity and efficiency of traditional electrocatalytic oxygen reduction synthesis H2O2 methods are solved, and efficient and low-cost H2O2 production is achieved, which significantly improves the catalytic performance.

CN119144990APending Publication Date: 2024-12-17EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411288195.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The traditional electrocatalytic redox synthesis method has low selectivity, yield and Faraday efficiency, and has problems such as high cost, high energy consumption and environmental pollution.

Method used

Using a method of preparing a catalytic material in which single atoms and nanoparticles coexist, the preparation of prepared by configuring an alkaline solution, adding phenols, aldehyde organics and Pd precursors to react at room temperature, followed by centrifugation and heating under a given atmosphere and temperature. Highly efficient catalytic materials are produced and used in electrocatalytic redox reactions.

Benefits of technology

High selectivity (up to 97%) and high yield (5.7mmol·g-1·h-1) and high Faraday efficiency (approximately 90%) are achieved, reducing energy consumption and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144990A_ABST
    Figure CN119144990A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a monatomic and nanoparticle coexisting catalytic material. The method comprises the following steps: preparing an alkaline solution and uniformly stirring; adding a phenolic organic matter, an aldehyde organic matter and a Pd precursor solution into the solution in sequence, and reacting at room temperature; centrifugally drying the reaction product to obtain powder; heating the powder under given atmosphere and temperature to obtain a catalytic material with coexistence of single atoms and nano-particles; the catalytic material is applied to a reaction for synthesizing H2O2 through electro-catalytic oxygen reduction. The preparation method has the beneficial effects of simple process, easily available raw materials and suitability for large-scale production; the Faraday efficiency is close to 90%, the stability can reach 20 hours, and the high performance is beneficial for reducing energy consumption and saving production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a method for preparing a catalytic material in which single atoms and nanoparticles coexist, and application thereof. Background Art

[0002] With the growing global demand for sustainable energy solutions, electrochemical synthesis processes, especially methods for efficiently generating H2O2, have become an important focus in the field of scientific research. As a green oxidant, H2O2 is widely used in pulp bleaching, wastewater treatment, and as a medium for oxygen reduction reactions in fuel cells due to its wide range of industrial applications and environmental friendliness. However, traditional anthraquinone chemical synthesis methods have disadvantages such as high cost, high energy consumption and environmental pollution. These problems have promoted the research on the electrochemical synthesis of H2O2. However, due to the lack of preparation technology, the selectivity, yield and Faradaic efficiency of electrocatalytic oxygen reduction synthesis of H2O2 are relatively low. Therefore, how to prepare catalysts with high selectivity, high yield and high Faradaic efficiency through simple preparation methods remains an important challenge. Summary of the invention

[0003] In order to solve the above problems, especially to address the deficiencies in the prior art, the present invention provides a method for preparing a catalytic material in which single atoms and nanoparticles coexist and an application thereof can solve the above problems.

[0004] To achieve the above purpose, the present invention adopts the following technical means:

[0005] A method for preparing a catalytic material in which single atoms and nanoparticles coexist, the method comprising the following steps:

[0006] (1) Prepare alkaline solution and stir evenly;

[0007] (2) adding phenolic organic matter, aldehyde organic matter and Pd precursor solution to the above solution in sequence and reacting at room temperature;

[0008] (3) centrifugally drying the reaction product to obtain a powder;

[0009] (4) The powder is heated in a given atmosphere and temperature, with a heating rate of 0.1 to 100°C / min, a heating temperature of 10 to 1200°C, and a heating time of 1 to 24 hours to obtain a catalytic material in which single atoms and nanoparticles coexist.

[0010] A further embodiment of the present invention is that the alkaline solution in step (1) is any one of an aqueous ammonia solution, an ethylenediamine solution, a hexamethylenetetramine solution, a sodium hydroxide solution, a sodium carbonate solution, and sodium bicarbonate.

[0011] A further embodiment of the present invention is that the concentration of the alkaline solution is 0.01-1%.

[0012] A further embodiment of the present invention is that the phenolic organic compound in step (2) is any one of phenol, catechol, resorcinol and phloroglucinol.

[0013] A further embodiment of the present invention is that the aldehyde organic compound in step (2) is any one of formaldehyde, acetaldehyde, benzaldehyde, phenylacetaldehyde and methylacetaldehyde.

[0014] A further embodiment of the present invention is that the Pd precursor in step (2) is any one of palladium acetate, palladium acetylacetonate, palladium nitrate, and potassium tetrachloropalladate.

[0015] A further solution of the present invention is that the ratio of the mass of the phenolic organic matter, the volume of the aldehyde organic matter and the mass of the Pd precursor in step (2) is 1 g: (0.01-100) mL: (0.001-10) g.

[0016] A further embodiment of the present invention is that the atmosphere in step (4) is any one of nitrogen, argon, helium, hydrogen and ammonia.

[0017] Another object of the present invention is to provide a catalytic material prepared by a method for preparing a catalytic material in which single atoms and nanoparticles coexist.

[0018] Another object of the present invention is to provide an application of the catalytic material of the present invention, wherein the catalytic material is applied in the electrocatalytic oxygen reduction reaction to synthesize H2O2, and the specific application is:

[0019] The catalytic material is 10-200ug·cm -2 The loading capacity is loaded on the reaction area of ​​0.196cm 2 The rotating ring disk electrode was placed on a rotating ring disk electrode and its disk current and ring current were tested at 1600 rpm in a 0.1 M KOH solution. The selectivity of oxygen reduction to synthesize H2O2 was calculated.

[0020] Or, the catalytic material is 50-500ug·cm -2 The loading capacity is loaded on the reaction area of ​​1cm 2 The hydrophobic carbon paper loaded with the catalytic material was placed in a flow cell for reaction. The reaction system was 75 mL of 0.1 M KOH solution, the oxygen flow rate was 30 sccm, and the electrolyte flow rate was 15 mL min -1 The test voltage is 0.1-0.3 V, and the product H2O2 is titrated with cerium sulfate to calculate its yield and Faraday efficiency.

[0021] Beneficial effects of the present invention:

[0022] The preparation method of the present invention has simple process, readily available raw materials and is suitable for large-scale production; the catalytic material prepared by the present invention shows excellent selectivity in synthesizing H2O2 by two-electron oxygen reduction, which is as high as 97%, and the actual yield of H2O2 in the flow cell can reach 5.7mmol·g -1 ·h -1 , the Faraday efficiency is close to 90% and the stability can reach 20 hours. Such high performance is conducive to reducing energy consumption and saving production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a transmission electron microscope image of the catalytic material of the present invention;

[0024] Figure 2 This is a spherical aberration electron microscope image of the catalytic material of the present invention;

[0025] Figure 3 is an X-ray diffraction pattern of the catalytic material of the present invention;

[0026] Figure 4 is a linear voltammetric curve diagram of the catalytic material of the present invention;

[0027] Figure 5 is a H2O2 selectivity curve diagram of the catalytic material of the present invention;

[0028] Figure 6 is a stability diagram of the catalytic material of the present invention;

[0029] Figure 7 Graph showing H2O2 yield and Faraday efficiency of the catalytic material of the present invention. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] A method for preparing a catalytic material in which single atoms and nanoparticles coexist, the method comprising the following steps:

[0033] (1) preparing an alkaline solution and stirring it evenly, wherein the alkaline solution is any one of an aqueous ammonia solution, an ethylenediamine solution, a hexamethylenetetramine solution, a sodium hydroxide solution, a sodium carbonate solution, and sodium bicarbonate, and the concentration of the alkaline solution is 0.01 to 1%;

[0034] (2) adding phenolic organic matter, aldehyde organic matter and Pd precursor solution to the above solution in sequence and reacting at room temperature, wherein the phenolic organic matter is any one of phenol, catechol, resorcinol and phloroglucinol, the aldehyde organic matter is any one of formaldehyde, acetaldehyde, benzaldehyde, phenylacetaldehyde and methylacetaldehyde, and the Pd precursor is any one of palladium acetate, palladium acetylacetonate, palladium nitrate and potassium tetrachloropalladate, and the ratio of the mass of the phenolic organic matter, the volume of the aldehyde organic matter and the mass of the Pd precursor is 1 g: (0.01-100) mL: (0.001-10) g;

[0035] (3) centrifugally drying the reaction product to obtain a powder;

[0036] (4) The powder is heated under a given atmosphere and temperature, wherein the atmosphere is any one of nitrogen, argon, helium, hydrogen, and ammonia, the heating rate is 0.1 to 100°C / min, the heating temperature is 10 to 1200°C, and the heating time is 1 to 24 hours, to obtain a catalytic material in which single atoms and nanoparticles coexist.

[0037] A method for preparing a catalytic material in which single atoms and nanoparticles coexist is used to prepare a catalytic material. The catalytic material is used in the electrocatalytic oxygen reduction reaction to synthesize H2O2. The specific application is: the catalytic material is heated to 10 to 200 ug·cm -2 The loading capacity is loaded on the reaction area of ​​0.196cm 2 The selectivity of oxygen reduction to H2O2 was calculated by rotating the catalytic material at 50-500 ug·cm -2 The loading capacity is loaded on the reaction area of ​​1cm 2 The hydrophobic carbon paper loaded with the catalytic material was placed in a flow cell for reaction. The reaction system was 75 mL of 0.1 M KOH solution, the oxygen flow rate was 30 sccm, and the electrolyte flow rate was 15 mL min -1 The test voltage is 0.1-0.3 V, and the product H2O2 is titrated with cerium sulfate to calculate its yield and Faraday efficiency.

[0038] Example 2

[0039] First, 90 mL of ethanol, 45 mL of ultrapure water and 0.45 mL of ethylenediamine were added to a 250 mL beaker in sequence and stirred for 30 minutes. Then 0.36 g of resorcinol was added to the above solution and stirring was continued for 30 minutes. During this period, 20 mg of acetylacetonate palladium was dissolved in 10 mL of ethanol and ultrasonicated until clear and transparent. Subsequently, 0.45 mL of formaldehyde and the above palladium solution were added to the above beaker and stirred at room temperature for 24 hours. The product was collected by centrifugation, washed three times with ultrapure water, and then dried and ground at 65 ° C to obtain a powder. Next, the above powder was calcined at 550 ° C for 2 hours in a tubular furnace under a flowing nitrogen atmosphere to obtain the catalytic material.

[0040] Example 3

[0041] First, 90 mL of ethanol, 45 mL of ultrapure water and 0.8 mL of sodium hydroxide were added to a 250 mL beaker in sequence and stirred for 30 minutes. Then 0.5 g of phenol was added to the above solution and stirring was continued for 30 minutes. During this period, 50 mg of potassium tetrachloropalladate was dissolved in 10 mL of ethanol and ultrasonicated until clear and transparent. Subsequently, 0.2 mL of benzaldehyde and the above palladium solution were added to the above beaker and stirred at room temperature for 12 hours. The product was collected by centrifugation, washed three times with ultrapure water, and then dried and ground at 65 ° C to obtain a powder. Next, the above powder was calcined at 750 ° C for 6 hours in a tubular furnace under a flowing argon atmosphere to obtain the catalytic material.

[0042] Example 4

[0043] First, 90 mL of ethanol, 45 mL of ultrapure water and 0.1 mL of hexamethylenetetramine were added to a 250 mL beaker in sequence and stirred for 30 minutes. Then 0.6 g of resorcinol was added to the above solution and stirring was continued for 30 minutes. During this period, 10 mg of palladium acetate was dissolved in 10 mL of ethanol and ultrasonicated until clear and transparent. Subsequently, 0.4 mL of acetaldehyde and the above palladium solution were added to the above beaker and stirred at room temperature for 12 hours. The product was collected by centrifugation, washed three times with ultrapure water, and then dried and ground at 65 ° C to obtain a powder. Next, the above powder was calcined at 850 ° C for 1 hour in a tubular furnace under a flowing hydrogen atmosphere to obtain the catalytic material.

[0044] Example 5

[0045] The catalytic material prepared in Example 1 (denoted as Pd NS NC550) was used to characterize the material structure and electrocatalytic oxygen reduction performance of H2O2:

[0046] (1) Figure 1 is the Pd prepared in Example 1NS The transmission electron microscopy image of the NC550 catalytic material shows that palladium nanoparticles exist on the surface of the catalytic material prepared in this example. Figure 2 It is Pd NS The spherical aberration electron microscope image of the NC550 catalytic material shows that there are single palladium atoms on the surface of the catalytic material prepared in this example. Figure 3 Yes Yes Pd NS The X-ray diffraction pattern of the NC550 catalytic material shows the presence of characteristic peaks of metallic palladium, indicating the presence of palladium nanoparticles. Therefore, through the material structure characterization of this example, it can be seen that the catalytic material in which palladium single atoms and nanoparticles coexist can be easily prepared through Example 1.

[0047] (2) Catalytic material was added at 50 ug·cm -2 The loading capacity is loaded on the reaction area of ​​0.196cm 2 The disk current and ring current were measured at 1600 rpm in a 0.1 M KOH solution. Figure 4 As shown, it can be seen that the catalytic material prepared by Example 1 has a larger ring current. Further calculations to obtain the selectivity of oxygen reduction synthesis of H2O2 are as follows: Figure 5 As shown, it can be seen that the selectivity of the catalytic material prepared by Example 1 is greater than 90% for H2O2 in a wide voltage window range of 0.1-0.7V. In addition, Figure 6 This is the stability test result of the catalytic material prepared in Example 1. It can be seen that the stability of the catalytic material during oxygen reduction synthesis of H2O2 can reach 20 hours.

[0048] (3) The catalytic material was heated to 200 ug cm -2 The loading capacity is loaded on the reaction area of ​​1cm 2 The hydrophobic carbon paper loaded with the catalytic material was placed in a flow cell for reaction. The reaction system was 75 mL of 0.1 M KOH solution, the oxygen flow rate was 30 sccm, and the electrolyte flow rate was 15 mL min -1 The test voltage is 0.1-0.3V. The product H2O2 is titrated with cerium sulfate to calculate its yield and Faraday efficiency. The results are as follows: Figure 7 As shown in the figure, it can be seen that the catalytic material prepared by Example 1 exhibits a very high H2O2 yield and Faraday efficiency in the voltage range of 0.1-0.3 V, especially at 0.1 V, it can reach the highest H2O2 yield of 5.7 mmol·g -1 ·h -1 , and the Faradaic efficiency is close to 90%.

[0049] The examples given in the present invention are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for preparing a catalytic material in which single atoms and nanoparticles coexist, characterized in that: The method comprises the following steps: (1) Prepare alkaline solution and stir evenly; (2) adding phenolic organic matter, aldehyde organic matter and Pd precursor solution to the above solution in sequence and reacting at room temperature; (3) centrifugally drying the reaction product to obtain a powder; (4) The powder is heated in a given atmosphere and temperature, with a heating rate of 0.1 to 100°C / min, a heating temperature of 10 to 1200°C, and a heating time of 1 to 24 hours to obtain a catalytic material in which single atoms and nanoparticles coexist.

2. The method for preparing a catalytic material in which single atoms and nanoparticles coexist according to claim 1, characterized in that: The alkaline solution in step (1) is any one of ammonia solution, ethylenediamine solution, hexamethylenetetramine, sodium hydroxide solution, sodium carbonate solution and sodium bicarbonate.

3. The method for preparing a catalytic material in which single atoms and nanoparticles coexist according to claim 1, characterized in that: The concentration of the alkaline solution is 0.01-1%.

4. The method for preparing a catalytic material in which single atoms and nanoparticles coexist according to claim 1, characterized in that: The phenolic organic compound in step (2) is any one of phenol, catechol, resorcinol and phloroglucinol.

5. The method for preparing a catalytic material in which single atoms and nanoparticles coexist according to claim 1, characterized in that: The aldehyde organic compound in step (2) is any one of formaldehyde, acetaldehyde, benzaldehyde, phenylacetaldehyde and methylacetaldehyde.

6. The method for preparing a catalytic material in which single atoms and nanoparticles coexist according to claim 1, characterized in that: The Pd precursor in step (2) is any one of palladium acetate, palladium acetylacetonate, palladium nitrate, and potassium tetrachloropalladate.

7. The method for preparing a catalytic material in which single atoms and nanoparticles coexist according to claim 1, characterized in that: The ratio of the mass of the phenolic organic matter, the volume of the aldehyde organic matter and the mass of the Pd precursor in step (2) is 1 g: (0.01-100) mL: (0.001-10) g.

8. The method for preparing a catalytic material in which single atoms and nanoparticles coexist according to claim 1, characterized in that: The atmosphere in step (4) is any one of nitrogen, argon, helium, hydrogen and ammonia.

9. A catalytic material prepared according to the method for preparing a catalytic material in which single atoms and nanoparticles coexist according to any one of claims 1 to 8.

10. The use of the catalytic material according to claim 9, characterized in that: The catalytic material is used in the electrocatalytic oxygen reduction reaction to synthesize H2O2, and the specific application is: The catalytic material is 10-200ug·cm -2 The loading capacity is loaded on the reaction area of ​​0.196cm 2 The rotating ring disk electrode was placed on a rotating ring disk electrode and its disk current and ring current were tested at 1600 rpm in a 0.1 M KOH solution. The selectivity of oxygen reduction to synthesize H2O2 was calculated. Or, the catalytic material is 50-500ug·cm -2 The loading capacity is loaded on the reaction area of ​​1cm 2 The hydrophobic carbon paper loaded with the catalytic material was placed in a flow cell for reaction. The reaction system was 75 mL of 0.1 M KOH solution, the oxygen flow rate was 30 sccm, and the electrolyte flow rate was 15 mL min -1 The test voltage is 0.1-0.3 V, and the product H2O2 is titrated with cerium sulfate to calculate its yield and Faraday efficiency.